A qualitative study of the stress autism mate app among autistic adults: user experiences and effects on stress awareness and coping skills - Hoeberichts, Kirsten; Roke, Yvette; Damen, Frank; Niks, Irene; Van Harten, Peter N. (Frontiers in Psychiatry, 2025)
IntroductionAutistic adults often face unique challenges in stress management. Conventional tools may not cater to their distinct needs. The Stress Autism Mate (SAM) app was developed to support stress recognition and promote active coping strategies through structured self-monitoring and personalised feedback. This study explored how autistic outpatient adolescents and adults experience the use of SAM in relation to stress awareness, coping behaviours, and engagement with digital tools.MethodsA qualitative phenomenological design was used, involving in-depth interviews with ten autistic participants (N = 10) who used SAM for at least four weeks. Reflexive thematic analysis was conducted to identify key patterns in user experiences.ResultsThree key processes were identified: (1) SAM facilitated increased awareness of previously unrecognised stress by externalising internal states, (2) participants shifted from avoidant to active coping strategies, supported by structured reflection and coping suggestions, and (3) the app’s emotionally neutral, predictable design created a safe and engaging space for self-regulation. However, tensions between structure and flexibility highlighted the need for greater personalisation to sustain engagement over time.DiscussionIn conclusion, SAM supports autistic individuals in transforming vague stress experiences into actionable insights, fostering emotional literacy and coping capacity. These findings extend prior quantitative evidence on SAM’s efficacy and provide actionable design recommendations for mHealth interventions aimed at neurodivergent populations.